Patah Titi and Substitute Heirs: A Study of Legal Pluralism on the Inheritance System in Aceh Community - Khairuddin Hasballah; Ridwan Nurdin; Muslim Zainuddin; Mutiara Fahmi (AHKAM : Jurnal Ilmu Syariah, 2021)
This research analyzes the issue of the practice of inheritance of patah titi and substitute heirs in Acehnese society according to the Compilation of Islamic Law (KHI), Islamic jurisprudence (fiqh) and local custom (adat). This empirical legal research uses a legal pluralism approach. Legal pluralism is a theory that analyzes the diversity of laws applicable and applied in the lives of society and the state. Data collection techniques include in-depth interviews and literature review. The findings reveal that the people of Aceh practice a religious legal system, which consists of the KHI, fiqh, and adat in the distribution of inheritance. In the customary law, the practice known as “patah titi” concerns the case of inheritance in which an heir predeceases the testator, thus preventing the heirs’ living descendants from receiving inheritance rights. The customary practice in regards to patah titi bears a similarity to fiqh, in which it does not recognize a substitute heir, as fiqh only recognizes the replacement of the heir’s position. According to ulamas and traditional leaders, the practice of patah titi causes a divergent of opinions in which some agree whereas others do not. Those who disagree are more likely to use the term “will”, meaning that even though grandchildren do not inherit, sometimes they get property by way of a will. Furthermore, substitute heirs as confirmed in the KHI, although unavailable in fiqh and adat literature, are still recognized as they are in accordance with maqāṣid sharīah (the objectives of Islamic law), i.e. for justice and benefit purposes. To conclude, such a practice is a consequence of legal pluralism, which prioritizes harmonization and integration between the three legal systems.   Abstrak: Penelitian ini menganalisis persoalan praktik pewarisan patah titi dan ahli waris pengganti dalam masyarakat Aceh menurut KHI (Kompilasi Hukum Islam), fikih, dan adat setempat. Penelitian hukum empiris ini menggunakan pendekatan pluralisme hukum. Teknik pengumpulan data meliputi wawancara mendalam dan studi pustaka. Temuan mengungkapkan bahwa masyarakat Aceh menganut sistem hukum agama, yang terdiri dari KHI, fikih, dan adat dalam pembagian warisan. Dalam hukum adat, praktik yang dikenal sebagai patah titi menyangkut kasus pewarisan di mana seorang ahli waris mendahului pewaris sehingga mencegah keturunan ahli waris yang masih hidup untuk menerima hak warisan. Kebiasaan patah titi memiliki kesamaan dengan fikih, yaitu tidak mengenal ahli waris pengganti, karena fikih hanya mengenal pengganti kedudukan ahli waris. Para ulama dan tokoh adat berpendapat bahwa praktik ini menyebabkan terjadinya perbedaan pendapat yang ada yang setuju dan ada yang tidak. Mereka yang tidak setuju lebih cenderung menggunakan istilah “wasiat”, artinya meskipun cucu tidak mewarisi, terkadang mereka mendapatkan harta dengan cara wasiat. Selanjutnya ahli waris pengganti yang ditegaskan dalam KHI, meskipun tidak ada dalam fikih dan literatur adat, tetap diakui sesuai dengan maqashid syariah (tujuan hukum Islam), yaitu untuk tujuan keadilan dan kemaslahatan. Kesimpulannya, praktik semacam itu merupakan konsekuensi dari pluralisme hukum yang mengutamakan harmonisasi dan integrasi antara ketiga sistem hukum tersebut.